Recurring Episodes of Thermal Stress Shift the Balance From a Dominant Host-Specialist to a Background Host-Generalist Zooxanthella in the Threatened Pillar Coral, Dendrogyra cylindrus - Lewis, Cynthia; Neely, Karen; Rodriguez-Lanetty, Mauricio (Frontiers in Marine Science, 2019)
Most scleractinian corals form obligate symbioses with photosynthetic dinoflagellates (family Symbiodiniaceae), which provide differential tolerances to their host. Previously, research has focused on the influence of symbiont composition and the dynamic processes of symbiont repopulation during single episodes of hyperthermal events, followed by years of less-stressful conditions. In contrast, this study characterized for the first time, the role of Symbiodiniaceae species changes in response to annually recurring hyperthermal events, a scenario soon expected to become the norm. Consecutive hyperthermal events during summer 2014 and 2015 along the Florida Reef Tract offered a unique opportunity to study bleaching susceptibility and recovery under recurrent annual hyperthermal scenarios. We utilized Illumina amplicon sequencing of the chloroplast 23S DNA region to assess with fine resolution the Symbiodiniaceae diversity associated with pillar coral, Dendrogyra cylindrus. Our findings show diverse assemblages of Symbiodiniaceae species and that some cryptic members are not transient associates but persistent and ecologically relevant, especially during recurrent annual warming events. This was evidenced by changes in relative abundance from the typically dominant host-specialist endosymbiont, Breviolum dendrogyrum, to B. meandrinium a host-generalist species common to corals in the family Meandrinidae but occurs at background densities in most coral colonies of D. cylindrus. The rise in abundance of B. meandrinium associated strongly with bleaching resistance in the coral host during two consecutive hyperthermal events. In some cases, host-compatible background symbionts can rapidly increase in abundance during episodes of stress and may impart physiological resilience to rapid environmental change; and thus, represents a potentially important ecological process by which symbiotic corals acclimatize to changing ocean conditions.